Respuesta :

Answer:

[tex]x=1, y=1, z=0[/tex]

Step-by-step explanation:

we have

[tex]-2x+2y+3z=0[/tex] ----> equation A

[tex]-2x-y+z=-3[/tex]  -----> equation B

[tex]2x+3y+3z=5[/tex] ----> equation C  

adds equation A and equation C

[tex]-2x+2y+3z=0\\2x+3y+3z=5\\-------\\2y+3y+3z+3z=0+5[/tex]

[tex]5y+6z=5[/tex] -----> equation D

adds equation B and equation C

[tex]-2x-y+z=-3\\2x+3y+3z=5\\--------\\-y+3y+z+3z=-3+5[/tex]

[tex]2y+4z=2[/tex] -----> equation E

we have the system

[tex]5y+6z=5[/tex] -----> equation D

[tex]2y+4z=2[/tex] -----> equation E

Multiply equation E by -1.5 both sides

[tex]-1.5(2y+4z)=-1.5(2)[/tex]

[tex]-3y-6z=-3[/tex] -----> equation F

adds equation D and equation F

[tex]5y+6z=5\\-3y-6z=-3\\---------\\5y-3y=5-3\\2y=2\\y=1[/tex]

Find the value of z

substitute the value of y in equation E (or substitute in equation D)

[tex]2(1)+4z=2[/tex]

[tex]2+4z=2[/tex]

[tex]4z=0[/tex]

[tex]z=0[/tex]

Find the value of x

substitute the value of y and z in equation A (or equation B or C)

[tex]-2x+2(1)+3(0)=0[/tex]

[tex]-2x+2=0[/tex]

[tex]-2x=-2[/tex]

[tex]x=1[/tex]

therefore

The solution of the system of equations is

[tex]x=1, y=1, z=0[/tex]